Workplace spirituality and nurses’ well-being: integrative review (2015-2025) - M. Fahrin Azhari; Johari Daud Makajil; Fredie Robinson; Muthmainnah Muthmainnah; Dwi Agustina; Winda Maolinda (International Journal of Public Health Science (IJPHS), 2026)
Occupational well-being and workforce sustainability in post-pandemic healthcare systems are at risk due to increasing emotional, ethical, and workload-related stressors that nurses encounter. Workplace spirituality has also been suggested as a protective factor, but empirical research remains fragmented and insufficiently synthesized. This integrative review aimed to synthesize the recent evidence on the role of workplace spirituality in the occupational well-being of nurses. A systematic search of Scopus, MEDLINE, and Cochrane databases identified English-language quantitative studies published between 2015 and 2025. Nineteen studies met the inclusion criteria and were synthesized using Whittemore and Knafl integrative review framework, with reporting relying on PRISMA 2020. There were five themes that included i) spirituality and burnout reduction, ii) organizational commitment and retention, iii) work engagement and job satisfaction, iv) spiritual congruence and interpersonal care, and v) spiritual leadership and well-being. Most findings demonstrated moderate-to-strong associations between workplace spirituality and decreased burnout, increased engagement, and greater organizational commitment. Nevertheless, these advantages were conditional and mitigated in the conditions of overwork, insufficiency of staffing, moral tension, and insufficient organizational support. This review offers a quantitative integrative synthesis of the first nursing-specific evidence to be published after the pandemic and shows that workplace spirituality serves as a complementary resource, rather than a standalone, to occupational well-being. The findings highlight important implications of nursing policy regarding introducing spirituality-based leadership development, ethical governance, and workforce support as part of the broader structural reforms.